2021
DOI: 10.32813/2179-1120.2021.v14.n1.a781
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome De Burnout Em Docentes E Discentes Universitários

Abstract: Objetivo: analisar a presença dos sintomas de burnout em docentes e discentes de Enfermagem em um ano de pandemia. Método: Trata-se de um estudo transversal, realizado online, com alunos e professores vinculados a uma instituição de ensino superior de Santa Catarina, em 2020. Para análise dos sintomas de burnout em docentes, foi utilizadoo Inventário de Burnout de Maslach, e para análise dos sintomas em discentes foiutilizado o Maslach Burnout Inventory Student Survey (MBI-SS). Resultados: Em 2020 o curso cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Just as the teaching workload is extrapolated beyond the classroom, Dallacosta and Castro (2021) also point out that university students also have extracurricular tasks that go beyond the hours that teaching activities normally demand. In the context of the pandemic, there is also a percentage of students who, due to economic and family issues, had to enter the world of work and deal with an intense weekly routine of studies and work activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Just as the teaching workload is extrapolated beyond the classroom, Dallacosta and Castro (2021) also point out that university students also have extracurricular tasks that go beyond the hours that teaching activities normally demand. In the context of the pandemic, there is also a percentage of students who, due to economic and family issues, had to enter the world of work and deal with an intense weekly routine of studies and work activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, for comparison purposes, when looking at the literature produced about the mental health of students and teachers during the pandemic period, Dallacosta and Castro (2021) point out that the dehumanization of work activities was not a preponderant factor for both, but rather the emotional exhaustion and the feeling of disbelief of their potential, although there is an interrelationship between all these factors. Adding to the comparative aspects, Becker et al ( 2021) conducted a literature review in which, through the analysis of 14 studies, an association was found between remote teaching and a higher prevalence of anxiety, stress, and Burnout in college students compared to face-to-face classes.…”
Section: Discussionmentioning
confidence: 99%